Academic success as willful-resistance: theorising with refugee-background students in Australia. Issue 3 (4th May 2021) - Ramos, Fabiane
ABSTRACT: This paper is about theorising with seven refugee-background youth, who have successfully completed their secondary studies in Australia. Using conversations-as-method, the focus is on how research partners theorise academic success, and on the reading I developed in response to their reflections. Inspired by the commonalities in Lugones' and Ahmed's work, especially their focus on persistence as an agentic stance in the face of adversity, I propose reading academic success in the context of this study as acts of willful-resistance (Spelling of 'willful' based on [Ahmed, S. (2012). Whiteness and the general will: Diversity work as willful work. philoSOPHIA, 2 (1), 1–20]). Here, willful-resistance is very much about students' persistence and a refusal to being reduced to victimised objects. In addition, academic success as willful-resistance works in coalition with other forces within/against layers of entangled contexts and oppressions/privileges.